Influence of Slip Condition on Unsteady Free Convection Flow of Viscous Fluid with Ramped Wall Temperature - Sami Ul Haq; Ilyas Khan; Farhad Ali; Arshad Khan; Tarek Nabil Ahmed Abdelhameed (Abstract and Applied Analysis)
The objective of this study is to explore the influence of wall slip condition on a free convection flow of an incompressible viscous fluid with heat transfer and ramped wall temperature. Exact solution of the problem is obtained by using Laplace transform technique. Graphical results to see the effects of Prandtl number Pr, time t, and slip parameter η on velocity and skin friction for the case of ramped and constant temperature of the plate are provided and discussed.